Examining barriers that predict mindfulness uptake in parents of children with autism spectrum disorder - Castells, Kara, author; Hepburn, Susan, advisor; Coatsworth, Doug, committee member; Brown, Samantha, committee member (Colorado State University. Libraries, 2020)
This study aimed to investigate barriers to mindfulness practice in parents of children with Autism Spectrum Disorder (ASD). I hypothesized that I could reliably measure three barriers to mindfulness that parents could rate themselves on statements reflecting these barriers. I also hypothesized that the barriers to mindfulness vary as a function of parent characteristics (e.g., overall experience with mindfulness, trait mindfulness, level of mindfulness experience) and child characteristics (e.g., severity of ASD symptoms) and that parents in this population are less likely to use mindfulness to reduce parent stress due to the perceived barriers, (1) misconceptions about mindfulness, (2) beliefs that parenting stress is not relevant to child outcomes, and (3) lack of time parents allocate to focus on their own well-being. The study surveyed 91 parents of children with ASD using a demographics questionnaire, the Mindfulness Barriers Scale (MBS), created by the research team, and the Mindful Attention and Awareness Scale. Preliminary analysis of the measure was conducted, followed by a series of independent sample t-tests, an ANOVA, and regression analysis to test the hypotheses. Examination of the MBS showed that each subscale was distinct in what they measured and showed acceptable reliability. Results showed that misconceptions, time, and disinterest in mindfulness, a single-item variable found as conceptually interesting in the preliminary analysis, were predictors of mindfulness uptake. Significant differences were found between the levels of mindfulness experience and misconceptions about mindfulness, parents with neutral or negative overall experience with mindfulness reported time as a greater barrier and higher misconceptions than parents with positive overall experience, and parents with low trait mindfulness reported time as a greater barrier than parents with high trait mindfulness. The significance of the findings, limitations, and future directions are discussed.
Keywords: developmental disabilities; parenting; mindfulness; autism spectrum disorder